Membrane Phosphoproteomics of Yeast Early Response to Acetic Acid: Role of Hrk1 Kinase and Lipid Biosynthetic Pathways, in Particular Sphingolipids - Guerreiro, Joana F.; Mira, Nuno P.; Santos, Aline X. S.; Riezman, Howard; Sá-Correia, Isabel (Frontiers in Microbiology, 2017)
Saccharomyces cerevisiae response and tolerance to acetic acid is critical in industrial biotechnology and in acidic food and beverages preservation. The HRK1 gene, encoding a protein kinase of unknown function belonging to the "Npr1-family" of kinases known to be involved in the regulation of plasma membrane transporters, is an important determinant of acetic acid tolerance. This study was performed to identify the alterations occurring in yeast membrane phosphoproteome profile during the adaptive early response to acetic acid stress (following 1h of exposure to a sub-lethal inhibitory concentration; 50 mM at pH 4.0) and the effect of HRK1 expression on the phosphoproteome. Results from mass spectrometry analysis following the prefractionation and specific enrichment of phosphorylated peptides using TiO2 beads highlight the contribution of processes related with translation, protein folding and processing, transport, and cellular homeostasis in yeast response to acetic acid stress, with particular relevance for changes in phosphorylation of transport-related proteins, found to be highly dependent on the Hrk1 kinase. Twenty different phosphoproteins known to be involved in lipid and sterol metabolism were found to be differently phosphorylated in response to acetic acid stress, including several phosphopeptides that had not previously been described as being phosphorylated. The suggested occurrence of cellular lipid composition remodeling during the short term yeast response to acetic acid was confirmed: Hrk1 kinase-independent reduction in phytoceramide levels and a reduction in phosphatidylcholine and phosphatidylinositol levels under acetic acid stress in the more susceptible hrk1Δ strain were revealed by a lipidomic analysis.